Thyroid abnormality in perimenopausal women with abnormal uterine bleeding - Byna, Prasanna; Siddula, Shireesha; Kolli, Swathi; Shaik, Mahaboob V. (International Journal of Research in Medical Sciences, 2017)
Background: AUB is a common but complicated clinical presentation and occurs in 15-20% of women between menarche to menopause and significantly affects the women’s health. Women with thyroid dysfunction often have menstrual irregularities, infertility and increased morbidity during pregnancy. The objective of present study is to find the correlation between thyroid disorders and AUB in perimenopausal women attending gynecology OPD. Methods: In the present study, fifty five patients with AUB were included and were evaluated for the cause including thyroid abnormality. Thyroid function tests were done in all patients. Results: Among 55 patients, 12 patients were diagnosed as hypothyroidism and 7 as hyperthyroidism, women with AUB 36 (65.4%) were euthyroid. Among 19 women with thyroid abnormality, heavy menstrual bleeding was seen in 8 (42%) women, 6 (31.57%) had polymenorrhagia, 5 (26.31%) had oligomenorrhoea. The frequent menstrual abnormality in women with hypothyroidism (12 women) was heavy menstrual bleeding in 5 (41.6%) women, 3 (25%) had oligomennorhoea, 4 (33.3%) had polymenorrhagia. Out of 7 women with hyperthyroidism, 2 (28.57%) had oligomenorrhoea, 3 (42.8%) had heavy menstrual bleeding, 2 (28.57%) had polymenorrhagia. In a total of 55 patients with AUB, 11 (20%) had structural abnormalities in uterus and ovaries. 5 (9%) had adenomyosis, 3 (5.4%) had ovarian cysts, 3 (5.4%) had fibroids. Conclusions: It is important to screen all women for thyroid abnormality who are presenting with AUB especially with non-structural causes of AUB. Correction of thyroid abnormalities also relieves AUB. This will avoid unnecessary hormonal treatment and surgery.